2013 Euromicro Conference on Digital System Design 2013
DOI: 10.1109/dsd.2013.120
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Energy Estimation of Application Specific Instruction-Set Processors

Abstract: Design space exploration for ASIP instruction-set design is a very complex problem, involving a large set of architectural choices. Existing methods are usually handcrafted and time-consuming. In this paper, we propose and investigate a rapid method to estimate the energy consumption of candidate architectures for VLIW ASIP processors. The proposed method avoids the time-consuming simulation of the candidate prototypes, without any loss of accuracy in the predicted energy consumption. We experimentally show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Our ASIP architecture exploration method builds upon our efficient method for energy estimation of ASIPs presented in [1]. In our previous research we have shown that accurate estimations of both the energy consumption and the applications cycle count can be obtained using only the assembly listing and the application profile.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Our ASIP architecture exploration method builds upon our efficient method for energy estimation of ASIPs presented in [1]. In our previous research we have shown that accurate estimations of both the energy consumption and the applications cycle count can be obtained using only the assembly listing and the application profile.…”
Section: Related Workmentioning
confidence: 99%
“…Combining these observations together with our efficient cost estimation technique allowed us to develop an efficient ASIP architecture exploration method which avoiding many simulation runs. In [1], we presented two variations of the cost estimation method: a) a completely static profile-based estimation, which performed a single simulation run and which handled only small changes in the profile, and b), a hybrid estimation which performed a separate simulation for each design but was still a more efficient method than the traditional trace-based cost analysis. However, our previous paper did not present any technique capable of automatically detecting when changes happen to the application profile, making it difficult to use the more efficient profile-based estimation in a reliable way.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations